TRANSFORMASI LINEAR PADA SUATU FUNGSI - Abidin, Wahyuni (Fakultas Sains dan Teknologi UIN ALauddin, 2014)
Linear transformation is one of the important branches of mathematics, especially linear transformation which has many applications in the problems of physics, engineering, social sciences, and various other branches of mathematics. The purpose of this study to determine a function that meets the requirements of linear transformations. The result is a transformation function that is not linear and linear